Identifying the Components of a Social Skills Curriculum with a Game-Based Approach in the Upper Elementary Level - Mousavifar, Parvin; Saadatmand, Zohreh; Baratali, Maryam (International Journal of Education and Cognitive Sciences, 2025)
Purpose: The aim of this study was to identify the components of a game-based social skills curriculum tailored for upper elementary education using a research synthesis approach grounded in Klein’s curriculum model. Methods and Materials: This research employed a qualitative research synthesis method based on analogical reasoning and Klein’s curriculum framework to extract and categorize curricular elements. The research corpus included 218 peer-reviewed articles and theses published between 2015 and 2025, both domestic and international, selected through purposive sampling until theoretical saturation was achieved. Inclusion criteria focused on studies with qualitative or qualitatively interpretable findings related to social skills instruction and game-based pedagogy. Data were analyzed thematically, and extracted components were organized into seven main curriculum elements: objectives, content, teaching-learning strategies, instructional activities, resources and tools, evaluation, and learning environment. Findings: The findings revealed a multidimensional framework for a game-based social skills curriculum. The objectives encompassed personal, interpersonal, emotional, and cognitive skill development, alongside innovation and employment readiness. Content included psychological, philosophical, and pedagogical foundations, while teaching strategies emphasized cooperative, reflective, and experiential learning through structured gameplay. Instructional activities highlighted curriculum planning and multimodal engagement. Resources involved both physical and digital infrastructures, including social media and interactive platforms. Evaluation addressed behavioral, emotional, and motivational assessment criteria. The learning environment included both physical and virtual spaces designed to support inclusive and dynamic social learning experiences. Conclusion: By synthesizing diverse theoretical and empirical foundations, the proposed curriculum model provides educators and policymakers with a practical, evidence-informed structure for integrating social-emotional learning into formal education through play.